Pengaruh Kemiringan Lereng terhadap Kerusakan Tanah di Giritontro, Wonogiri - MUJIYO, MUJIYO; LARASATI, WIDHI; WIDIJANTO, HERY; HERAWATI, AKTAVIA (Agrotrop : Journal on Agriculture Science, 2021)
The Effect of Slope Gradient of land on the Soil Damage in Giritontro, Wonogiri . Soil degradation is one of the problems in agriculture that affects the level of quality and carrying capacity of the soil for certain land uses. This study aims to analyse the status of soil degradation, the effect of slope, the determinant factor, and recommendation for land management.It was conducted in Giritontro District, Wonogiri Regencywith survey methods by field verification, taking soil samples and laboratoryanalysis based on Regulation of The Government of Indonesia Number 150 of 2000. Analysis unit is land map unit (LMU) which obtained from an overlay of mapssoil types, slope, rainfall, and land use. There were 12 LMU, and repeated 3 site samplings in each it. The result shows that the status of soil degradation was classified as slightly degraded (R.I) in all area research of 5.016.37 ha. The slope has a very significant effect on soil degradation. Slope 26-40% has significant highest score of soil degradration. Determinant factors were soil bulk density and porosity, therefore giving organic matter and optimizing tillage were recommended to improve land quality.